Non-alcoholic fatty liver disease (NAFLD) in different populations: A clinical and epidemiological study – sample of São José do Rio Preto - Andrade,Gabriel Costa de (2016)
SUMMARY Introduction: NAFLD is an heterogeneous condition that includes steatosis and non-alcoholic steatohepatitis (NASH), in the absence of significant alcohol consumption, reaching 30% of the population. The most common risk factors are: age, gender, ethnicity, diabetes mellitus (DM), obesity, predisposition, metabolic syndrome (MS), insulin resistance (IR), drugs, and polycystic ovary syndrome. Objective: To describe the profile of patients with NAFLD seen at Hospital de Base of Rio Preto, in the state of São Paulo. Method: Patients with NAFLD were assessed, with medical and epidemiological data collected after informed consent. Results: Of the 62 patients evaluated, 76% were women, 73% Caucasians, and 71% were aged between 50 and 69 years and had no symptoms. Ultrasonography results showed steatosis in 84%. NASH was diagnosed in 61% of the sample. 21 patients underwent liver biopsy, of which 36% had cirrhosis, 1 had liver cancer, and 1 pure steatosis (5% each). Risk factors were found in 70% of patients with metabolic syndrome, 87% with increased waist circumference, 63% with dyslipidemia, 61% (n=38) with high blood pressure (HBP), 28% with DM, 52% physically inactive, and 44% with insulin resistance (IR) (HOMA> 3.5). There was an association between IR and NASH (p=0.013), IR and obesity (p=0.027), IR and MS (p=0.006), and MS and steatosis on medical ultrasound (USG) (p=0.014). Conclusion: The most frequent risk factors were MS and its variables: increased waist circumference, dyslipidemia and HBP. This underscores the importance of metabolic control in NAFLD and confirms its role as the hepatic component of metabolic syndrome.